2018
DOI: 10.1111/eci.12967
|View full text |Cite
|
Sign up to set email alerts
|

Priming and de‐priming of neutrophil responses in vitro and in vivo

Abstract: The activation status of neutrophils can cycle from basal through primed to fully activated ("green-amber-red"), and at least in vitro, primed cells can spontaneously revert to a near basal phenotype. This broad range of neutrophil responsiveness confers extensive functional flexibility, allowing neutrophils to respond rapidly and appropriately to varied and evolving threats throughout the body. Primed and activated cells display dramatically enhanced bactericidal capacity (including augmented respiratory burs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
86
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(102 citation statements)
references
References 64 publications
(113 reference statements)
2
86
2
1
Order By: Relevance
“…As the first responders to infection, neutrophils require highly tuned functional flexibility. The ability to change functional status in response to immune‐modulators allows the neutrophil to patrol the body in a relatively quiescent state while remaining capable of sensing and then employing appropriate responses when threats arise . When quiescent or un‐primed neutrophils are exposed to certain proinflammatory cytokines or chemokines (e.g., TNF, fMLF, platelet‐activating factor [PAF], and GM‐CSF), they transition into a primed state.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the first responders to infection, neutrophils require highly tuned functional flexibility. The ability to change functional status in response to immune‐modulators allows the neutrophil to patrol the body in a relatively quiescent state while remaining capable of sensing and then employing appropriate responses when threats arise . When quiescent or un‐primed neutrophils are exposed to certain proinflammatory cytokines or chemokines (e.g., TNF, fMLF, platelet‐activating factor [PAF], and GM‐CSF), they transition into a primed state.…”
Section: Introductionmentioning
confidence: 99%
“…The ability to change functional status in response to immune-modulators allows the neutrophil to patrol the body in a relatively quiescent state while remaining capable of sensing and then employing appropriate responses when threats arise. 1 When quiescent or un-primed neutrophils are exposed to certain proinflammatory cytokines or chemokines (e.g., TNF, fMLF, platelet-activating factor In addition to the described functional and biochemical changes, neutrophils undergoing activation exhibit morpho-rheological (MORE) changes to their biophysical shape. It has been reported that activated neutrophils are smaller and stiffer than their unactivated and un-primed counterparts, [10][11][12][13] although there exist conflicting reports of neutrophils expanding poststimulation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, neutrophil–hepatic stellate cell (HSC) interactions may drive the progression of liver fibrosis in experimental steatohepatitis . Emerging evidence suggests that neutrophil activation and functions are regulated by many proinflammatory mediators, cytokines, growth factors, transcription factors, and epigenetic factors (e.g., microRNAs [miRNAs]) . Among miRNAs, microRNA‐223 (miR‐223) is expressed at the highest levels in neutrophils, playing a critical role in attenuating neutrophil maturation and activation .…”
mentioning
confidence: 99%
“…Our earlier studies have demonstrated that such secretory organelles containing CD11b, FPR1and, FPR2 are mobilized to the neutrophil surface by priming agents such as TNFα and LPS [65][66][67]. Considering the high levels of TNFα in a number of inflammatory diseases such as rheumatoid arthritis, suggests that the mechanism underlying the neutrophil priming process and its consequences both in vitro and in vivo may offer new opportunities for therapeutic intervention in pathological settings [68]. Despite the robust release of ROS induced by low nM concentrations of RE, much higher concentrations were needed to induce neutrophil chemotaxis.…”
Section: Discussionmentioning
confidence: 99%